Lrrk2 mutations in South America: A study of Chilean Parkinson's disease - Perez-Pastene, Carolina (2007)
Pathogenic substitutions in the leucine-rich repeat kinase 2 protein (Lrrk2), R1441G and G2019S, are a prevalent cause of autosomal dominant and sporadic Parkinson's disease in the Northern Spanish population. In this study we examined the frequency of these two substitutions in 166 Parkinson's disease patients and 153 controls from Chile, a population with Spanish/European-Amerindian admixture. Lrrk2 R1441G was not observed, however Lrrk2 G2019S was detected in one familial and four sporadic Parkinson's disease patients. These findings suggest Lrrk2 G2019S may play an important role in Parkinson's disease on the South American Continent and further studies are now warranted.